PENGARUH PENGGUNAAN PLATFORM SEESAW TERHADAP LITERASI DIGITAL SISWA KELAS IV SD - Yani Setiyawati; Murjainah; Aan Suriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using the Seesaw platform on the digital literacy of fourth-grade students at SD Negeri 34 Palembang. The research was motivated by the low level of students' digital literacy and the suboptimal use of technology in the learning process. The Seesaw platform was chosen because it offers a digital portfolio-based learning environment that fosters active engagement among teachers, students, and parents. The method used in this study was an experimental design with a pretest-posttest control group approach. The research subjects consisted of two classes, class IVA as the experimental group and class IVB as the control group, with 29 students in each. The experimental group received instruction using Seesaw, while the control group was taught using conventional methods. Data were collected through multiple-choice tests to assess students' digital literacy levels before and after the treatment. The analysis results showed an increase in the average digital literacy score in the experimental class from 58.97 to 76.55, while the control class improved from 53.45 to 65.52. A hypothesis test using the Independent Sample t-Test yielded a t-value of 7.588 with a significance level of 0.000 (< 0.05), indicating that H₀ was rejected and Hₐ was accepted. This confirms a significant effect of using Seesaw on enhancing students' digital literacy. Furthermore, Seesaw-based learning was found to be more engaging and interactive, thereby improving students’ participation and understanding of the lesson content.